FAKTOR PENENTU INSTABILITAS HARGA PRODUK BERBASIS IMPOR (Kedele dan Gula) - Yati Nuryati; Yudha Hadian Nur; Dwi Wahyuniarti Prabowo (Buletin Ilmiah Litbang Perdagangan, 2010)
Price stability of staple food needs is one of the government’s policy priorities in anticipating the negative impact of the global economic crisis. Price instability in the long term could impact on high inflation, falling of purchasing power and political manipulation that would interfere the availability of strategic food products. The high price of staple food needs will certainly disturb the national food security. The aims of ths study is analyzing the factors that influence the instability of soybean and sugar price and determine how domestic patterns of integration and the price mechanism, as well as offering the necessary policy formulation related to the stabilization effort on imported base of staple food needs. Analysis using descriptive qualitative and quantitative dynamic econometric model that is structural vector autoregression (sVAR) and error correction model (ECM) using monthly time series data in 2000-2009. There is a strong integration between the world market commodity prices with price stability of soybean and sugar prices where transmission occurs in about 2-14 months. World price shocks and the impact of imports on price increases and reaches equilibrium at a higher price level. The mechanism of the international market is still strong enough to affect soybean and sugar domestic market. The implication show that price on imported base product such as sugar and soybeans still necessary to be implemented.